2018
DOI: 10.1155/2018/6987435
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Unlicensed Drug Vendor Practices Related to Childhood Malaria in One Rural District of Uganda: An Exploratory Study

Abstract: This study investigated unlicensed drug outlets' practices for the management of malaria in the rural district of Butaleja, Uganda. A qualitative design using semistructured interviews was used. Interviews were recorded, translated, transcribed, and analyzed using thematic analysis. A total of 75 vendors, representing 85% of the outlets in the study area, were interviewed. Most of the vendors were associated with a drug shop type of outfit. About three-quarters reported having completed some level of postsecon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In some instances, many purchased only partial treatment regimens because this is all that they could afford. Consequently, in Butaleja District where the majority of informal outlets are managed by untrained vendors and have unreliable ACT stocks, case management routinely falls short of the national malaria treatment guidelines 5,25,27,50,60,61. Despite the government’s assurance of free access to diagnostics and medications at public facilities, this and other studies demonstrate that national policies in many such regions are not translated at the community level 5,23,25,43,47,53,62,63.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some instances, many purchased only partial treatment regimens because this is all that they could afford. Consequently, in Butaleja District where the majority of informal outlets are managed by untrained vendors and have unreliable ACT stocks, case management routinely falls short of the national malaria treatment guidelines 5,25,27,50,60,61. Despite the government’s assurance of free access to diagnostics and medications at public facilities, this and other studies demonstrate that national policies in many such regions are not translated at the community level 5,23,25,43,47,53,62,63.…”
Section: Discussionmentioning
confidence: 99%
“…While not yet implemented in Butaleja, some districts in Uganda have a network of level I HCs comprised of volunteer CHWs at the village level trained to deliver integrated community case management (iCCM) (K Mweru, MD, District Officer, personal communication, April 2011). With no pharmacies and a few licensed drug shops located mainly in town centers and market areas, many households are reliant on the predominant informal (unlicensed) drug outlets for health care and western medicines 23,25,27. For the purpose of this study, informal retail drug outlets are defined as mobile or stationary commercial settings, such as markets and shops, which sell antimalarials but are not registered with any government regulatory body and operate outside the purview of regulation, registration, or oversight by the government or other health or professional institutions 28…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of quality medicines is critical for promoting trust among users and improving health outcomes. A study by [ 30 ] showed that there are more 84.3% PFP provider drug outlets compared to 13.0% public providers. Many of these PFP facilities are unlicensed and unsupervised by the relevant authorities [ 12 ].…”
Section: Main Textmentioning
confidence: 99%
“…45,50,51 Several recommendations are suggested, such as: the provision of continuing training, supervision, and monitoring from the government; an enhanced collaboration with healthcare workers (including for referrals); a greater compliance with national policies and guidelines that also need to be better disseminated; a better access to proper information; and the need for community awareness whose demand is a strong determinant of medicine retailers' service provision practices. [52][53][54][55][56][57][58][59][60] Two other focuses reinforce the attention paid to medicine retailers within the health systems: profession and regulation, and impact studies. With 79 studies, these two focuses accounted for approximately a quarter of the included studies (27%).…”
Section: Three Professional Groups Of Medicine Retailersmentioning
confidence: 99%